Violent Asphyxial Death: A Study in Dinajpur Medical College, Dinajpur (Journal of Enam Medical College, 2013)
Background: The word asphyxia is now commonly used to describe a range of conditions for which the lack of oxygen whether it is partial (hypoxia) or complete (anoxia) is considered to be the cause. The cardinal signs of asphyxia are cyanosis, congestion and petechial haemorrhage. Objective: To investigate the causes and manner of asphyxial death. Materials and Methods: It was a retrospective study conducted in the department of Forensic Medicine, Dinajpur Medical College, Dinajpur during July 2004 to June 2006. A total of 96 cases were examined and recorded. These cases were brought to the morgue of Dinajpur Medical College from 13 different police stations and 1 railway GRP station of Dinajpur district. The data were collected from the autopsy reports (preserved third copy) with permission of the concerned autopsy surgeons. Results: 88.55% of asphyxia deaths were due to hanging, 6.25% due to strangulation and 5.20% were due to suffocation. Conclusion: Most of the asphyxial deaths are due to hanging. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 91-93 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16131